The new Oxford Shakespeare : the complete works / William Shakespeare ; general editors, Gary Taylor, John Jowett, Terri Bourus, Gabriel Egan ; associate editors, Francis X. Connor, Rory Loughnane, Anna Pruitt ; assistant editor, Sarah Neville, Will Sharpe. - Shakespeare, William, 1564-1616 (Oxford University Press, 2016)
A completely new modern-spelling edition of all of Shakespeare's plays and poems, edited afresh from the original texts. With extensive introductions and on-page notes, it gives students and theatre-lovers the very best resources to understand and enjoy Shakespeare's works.